Portrayal of accompanying family members of children and teenagers cared for retinoblastoma in Brazil: A cross-sectional study (Research, Society and Development, 2021)
Retinoblastoma is the most common intraocular tumor in childhood. It is not yet clear who the accompanying family members of affected children and teenagers are, how they find out about the disease, or how satisfied they are with the guidance provided by healthcare providers. Thus, this study aimed to portray the family members of children and teenagers with retinoblastoma regarding their sociodemographic aspects, the sources of information used by them to learn about the disease, their satisfaction with the guidance received from healthcare providers regarding this form of cancer, and to analyze whether there is an association between these variables. It was a cross-sectional, descriptive-analytical study, via web survey in Brazil, based on social media and analysis by descriptive-inferential statistics. A total of 129 people participated in this study, with an average age of 34.61 years, most of them were mothers, housewives, with eleven years of education, with a family income not exceeding minimum wage, and living mostly in the southeastern region of Brazil. Among the respondents, 65.12% of them stated that they use websites as their main source of information. Regarding the satisfaction with the guidance received from healthcare providers, there were scores above eight, indicating a high level of satisfaction with the instructional activity of physicians and nurses. It is concluded, in addition to the sociodemographic portrayal achieved, that websites emerged as the main source of information on retinoblastoma and that there was high satisfaction regarding the guidance received from healthcare providers. There was an association between family members whose occupation was considered to be that of a housewife and the use of social media as the main source of information regarding retinoblastoma, as well as an association between being self-employed and the satisfaction with the guidance provided by physicians regarding the disease.